Meningkatkan Kemampuan Menyimpulkan Isi Berita dengan Metode Diskusi pada Siswa Kelas VIII SMP Negeri Fatumfaun - Yoseph Moruk (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2018)
Concluding ability of news content is one of basic competences that should be mastered by the students at second grade of national junior high school Fatumfaun. However, based on observation toward students ability in concluding news content is still in low category. It is caused by inappropriate method used by teacher. This research aims at increasing students’ ability in concluding news content by suing discussion method in academic year 2017/2018. Class action research was used in this research by using observation, written test and scrutinize test of read news text in collecting data. Data source in this research is the students at second grade of national junior high school Fatumfaun in academic year 2017/2018. Based on research result, it is found that students’ ability in concluding news content by using discussion method in first cycle, the students get average score about 40.4 while in second cycle about 82.4 that included in very good category.